Biocompatibility of gold nanoparticles and their endocytotic fate inside the cellular compartment: a microscopic overview - Shukla, Ravi; Bansal, Vipul; Chaudhary, Manakshi; Basu, Atanu; Bhonde, Ramesh R.; Sastry, Murali (Langmuir, 2005)
Macrophages are one of the principal immune effector cells that play essential roles as secretory, phagocytic, and antigen-presenting cells in the immune system. In this study, we address the issue of cytotoxicity and immunogenic effects of gold nanoparticles on RAW264.7 macrophage cells. The cytotoxicity of gold nanoparticles has been correlated with a detailed study of their endocytotic uptake using various microscopy tools such as atomic force microscopy (AFM), confocal-laser-scanning microscopy (CFLSM), and transmission electron microscopy (TEM). Our findings suggest that Au(0) nanoparticles are not cytotoxic, reduce the production of reactive oxygen and nitrite species, and do not elicit secretion of proinflammatory cytokines TNF-alpha and IL1-, making them suitable candidates for nanomedicine. AFM measurements suggest that gold nanoparticles are internalized inside the cell via a mechanism involving pinocytosis, while CFLSM and TEM studies indicate their internalization in lysosomal bodies arranged in perinuclear fashion. Our studies thus underline the noncytotoxic, nonimmunogenic, and biocompatible properties ofgold nanoparticles with the potential for application in nanoimmunology, nanomedicine, and nanobiotechnology.

Bioleaching of sand by the fungus fusarium oxysporum as a means of producing extracellular silica nanoparticles - Bansal, Vipul; Sanyal, A.; Rautaray, D.; Ahmad, Absar; Sastry, Murali (Advanced Materials, 2005)
A plant pathogenic fungus, Fusarium oxysporum, can be used as a biological model system for the extracellular bioleaching of hollow spherical silica nanoparticles (see Figure) from sand. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential waste materials could lead to eco-friendly and economically viable methods for the large-scale synthesis of nanomaterials.

Fungus-mediated biosynthesis of silica and titania particles - Bansal, Vipul; Rautaray, D.; Bharde, Atul A.; Ahire, Kedar C.; Sanyal, A.; Ahmad, Absar; Sastry, Murali (Journal of Materials Chemistry, 2005)
The synthesis of inorganic materials by biological systems is characterized by processes that occur at close to ambient temperatures, pressures and neutral pH. This is exemplified by biosilicification in marine organisms such as diatoms while laboratory-based synthesis of silica involves extreme temperature and pH conditions. We show here that silica and titania particles may be produced by challenging the fungus Fusarium oxysporum with aqueous anionic complexes SiF62- and TiF62- respectively. Extra-cellular protein-mediated hydrolysis of the anionic complexes results in the facile room temperature synthesis of crystalline titania particles while calcination at 300 degrees C is required for crystallization of silica.

Heavy-metal remediation by a fungus as a means of production of lead and cadmium carbonate crystals - Sanyal, A.; Rautaray, D.; Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Langmuir, 2005)
We show here that reaction of the fungus, Fusarium oxysporum, with the aqueous heavy-metal ions Pb2+ and Cd2+ results in the one-step formation of the corresponding metal carbonates. The metal carbonates are formed by reaction of the heavy-metal ions with CO2 produced by the fungus during metabolism and thus provide a completely biological method for production of crystals of metal carbonates. The PbCO3 and CdCO3 crystals thus produced have interesting morphologies that are shown to arise because of interaction of the growing crystals with specific proteins secreted by the fungus during reaction. An additional advantage of this approach is that the reaction leads to detoxification of the aqueous solution and could have immense potential for bioremediation of heavy metals. Under conditions of this study, the metal ions are not toxic to the fungus, which readily grows after exposure to the metal ions.

Fungus-mediated biotransformation of amorphous silica in rice husk to nanocrystalline silica - Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Journal of American Chemical Society, 2006)
Rice husk is a cheap agro-based waste material, which harbors a substantial amount of silica in the form of amorphous hydrated silica grains. However, there have been no attempts at harnessing the enormous amount of amorphous silica present in rice husk and its room-temperature biotransformation into crystalline silica nanoparticles. In this study, we address this issue and describe how naturally deposited amorphous biosilica in rice husk can be bioleached and simultaneously biotransformed into high value crystalline silica nanoparticles. We show here that the fungus Fusarium oxysporum rapidly biotransforms the naturally occurring amorphous plant biosilica into crystalline silica and leach out silica extracellularly at room temperature in the form of 2-6 nm quasi-spherical, highly crystalline silica nanoparticles capped by stabilizing proteins; that the nanoparticles are released into solution is an advantage of this process with significant application and commercial potential. Calcination of the silica nanoparticles leads to loss of occluded protein and to an apparently porous structure often of cubic morphology. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential cheap agro-industrial waste materials is an exciting possibility and could lead to an energy-conserving and economically viable green approach toward the large-scale synthesis of oxide nanomaterials.

Room-temperature biosynthesis of ferroelectric barium titanate nanoparticles - Bansal, Vipul; Poddar, Pankaj; Ahmad, Absar; Sastry, Murali (Journal of the American Chemical Society, 2006)
The syntheses of inorganic materials by biological systems is characterized by processes that occur close to ambient temperatures, pressures, and neutral pH, as is exemplified by biosilicification and biomineralization processes in nature. Conversely, laboratory-based syntheses of oxide materials often require extremes of temperature and pressure. We have shown here the extracellular, room-temperature biosynthesis of 4-5 nm ternary oxide nanoparticles such as barium titanate (BT) using a fungus-mediated approach. The tetragonality as well as a lowered Curie transition temperature in sub-10 nm particles was established, and the ferroelectricity in these particles was shown using Kelvin probe microscopy.

Zirconia enrichment in zircon sand by selective fungus-mediated bioleaching of silica - Bansal, Vipul; Syed, Asad; Bhargava, Suresh Kumar; Ahmad, Absar; Sastry, Murali (Langmuir, 2007)
One of the important routes for the production of zirconia is by chemical treatment and removal of silica from zircon sand (ZrSixOy). We present here a completely green chemistry approach toward enrichment of zirconia in zircon sand; this is based on the reaction of the fungus Fusarium oxysporum with zircon sand by a process of selective extracellular bioleaching of silica nanoparticles. Since this reaction does not result in zirconia being simultaneously leached out from the sand, there is a consequent enrichment of the zirconia component in zircon sand. We believe that fungal enzymes specifically hydrolyze the silicates present in the sand to form silicic acid, which on condensation by certain other fungal enzymes results in room-temperature synthesis of silica nanoparticles. This fungus-mediated twofold approach might have vast commercial implications in low-cost, ecofriendly, room-temperature syntheses of technologically important oxide nanomaterials from potentially cheap naturally available raw materials like zircon sand.

Self–assembled histidine acid phosphate nanocapsules as templates for multifunctional hollow platinum nanospheres in ionic liquid [BMIM][BF 4 ] for drug delivery - Soni, Sarvesh Kumar; Sarkar, Sampa; Sarkar, Dhiman; Coloe, Peter J.; Bhargava, Suresh Kumar; Bansal, Vipul (Proceedings of Chemeca, 2012)
During the past few decades, the design and fabrication of nano drug delivery vehicle has received considerable attention for incorporating multi-functionality, emphasizing transportation of anticancer drugs to tumour sites. Protein-based nanoparticles hold significant promise in the development of anticancer drug delivery systems since they have remarkable superiority in biocompatibility, biodegradability and natural metabolism in physiologic systems. Ionic liquids (ILs) are a class of solvents that are composed solely of ions (ILs – commonly referred as room temperature molten salts or room temperature ionic liquids). They have recently emerged as green solvents or green reaction media, because of their reported unique physico-chemical properties. We report for the first time the controlled self-assembly of Histidine Acid phosphatase (HAP) enzyme in the IL 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF 4 ], leading to the formation of HAP nanocapsules as template for synthesis of platinum nanospheres. These HAP nano-containers were loaded with an anticancer drug curcumin. We further demonstrated in vitro drug release and synergistic anticancer effect of these systems on three different cell lines viz. hepatocellular carcinoma (HepG2), breast cancer (MCF-7) and human acute monocytes (THP-1). The present work can extend our theoretical understanding on nano-bio interfacial molecular self assembly and will facilitate the motivated insights of inorganic/organic hybrid nano-materials/ nano-particles/ nano-objects and ionic liquids based multi functional drug delivery vehicles with synergistic combination chemotherapy for potential application in tumor targeting. INTRODUCTION During the past few decades, the design and fabrication of drug delivery vehicle has received considerable attention for incorporating multi-functionality emphasizing transportation of anticancer drugs to tumour sites. These nano drug delivery vehicles have many advantages including prolonged circulation time of the drugs (Duncan, 2003, Kiick, 2007) , improved drug targeting and solubility (Duncan, 2003, Kiick, 2007), higher payloads (Duncan, 2003) and controlled release of the therapeutics into the blood stream or the targeted tumour tissues (Uhrich et al. 1999, Duncan, 2003).

Charge-switchable gold nanoparticles for enhanced enzymatic thermostability - Shankar, Shiv; Soni, Sarvesh K.; Daima, Hemant K.; Selvakannan, P. R.; Khire, Jayant Malhar; Bhargava, Suresh Kumar; Bansal, Vipul (Physical Chemistry Chemical Physics, 2015)
This study illustrates a facile strategy for efficient immobilization of enzymes on a metal nanoparticle surface. The strategy proposed here enables the enzymatic activity to be retained while increasing the enzyme thermostability. It is demonstrated that the use of a zwitterionic amino acid tyrosine as a reducing and capping agent to synthesise gold nanoparticles allows efficient immobilization of phytase enzyme through charge-switchable electrostatic interactions. The detailed kinetic and thermodynamic studies reveal that the proposed enzyme immobilization strategy improves the overall quality of phytase by reducing the activation energy required for substrate hydrolysis and broadening the temperature window in which immobilized enzyme is able to operate. The outcomes of this study indicate that the underlying zwitterionic nature of 20 natural amino acids along with significant variability in their isoelectric points and hydropathy indices as well the ability of some of the amino acids to reduce metal ions is likely to offer significant opportunities for tailoring nano-bio interfaces in a rational manner for a range of biological applications.